Structure and vascularization of the cruciate ligaments of the human knee joint - Petersen, Wolf; Tillmann, B. (Anatomy and Embryology, 1999)
The structure and vascularization of the human anterior and posterior cruciate ligament were investigated by light microscopy, transmission electron microscopy,, injection techniques and by immunohistochemistry. The major part of the anterior and posterior cruciate ligament is composed of bundles of type I collagen. Type III collagen-positive fibrils separate the bundles. The major cell type is the elongated fibroblast, lying solitarily between the parallel collagen fibrils. The histologic structure of the cruciate ligaments is not homogeneous. In both ligaments there is a zone where the tissue resembles fibrocartilage. In the anterior cruciate ligament the fibrocartilaginous zone is located 5-10 mm proximal of the tibial ligament insertion in the anterior portion of the ligament. In the posterior cruciate ligament the fibrocartilage is located in the central part of the middle third. Within those zones the cells are arranged in columns and the cell shape is round to ovoid. Transmission electron microscopy reveals typical features of chondrocytes. The chondrocytes are surrounded by a felt-like pericellular matrix, a high content of cellular organelles and short processes on the cell surface. The pericellular collagen is positive for type II collagen. The major blood supply of the cruciate ligaments arises from the middle geniculate artery. The distal part of both cruciate ligaments is vascularized by branches of the lateral and medial inferior geniculate artery. Both ligaments are surrounded by a synovial fold where the terminal branches of the middle and inferior arteries form a periligamentous network. From the synovial sheath blood vessels penetrate the ligament in a horizontal direction and anastomose with a longitudinally orientated intraligamentous vascular network. The density of blood vessels within the ligaments is not homogeneous. In the anterior cruciate ligament an avascular zone is located within the fibrocartilage of the anterior part where the ligament faces the anterior rim of the intercondylar fossa. The fibrocartilaginous zone of the middle third of the posterior cruciate ligament is also avascular. According to Pauwel's theory of the "causal histogenesis" (1960) the stimulus for the development of fibrocartilage within dense connective tissue is shearing and compressive stress. In the anterior cruciate ligament this biomechanical situation may occur when the ligament impinges on the anterior rim of the intercondylar fossa when the knee is fully extended. Compressive and shearing stress in the center of the middle third of the posterior cruciate ligament may result from twisting of the fiber bundles.